A primer for clinical researchers in the emergency department: Part V: How to describe data and basic medical statistics. (5th December 2012) - Donath, Susan; Davidson, Andrew; Babl, Franz E
Abstract In this series we address key topics for clinicians who conduct research as part of their work in the ED. In this section we will address important statistical concepts for clinical researchers and readers of clinical research publications. We use practical clinical examples of how to describe clinical data for presentation and publication, and explain key statistical concepts and tests clinical researchers will likely use for the majority of ED datasets.